Gitelman Syndrome in a 37-Years Old Woman with Urinary Tract Syndrome and History of Caesarean Section: A Case Report - Hutomo, Yudhistira; Widjaja, Dipdo Petrus (Riviera Publishing, 2024)
Gitelman Syndrome (GS) is a rare genetic disorder often underdiagnosed due to its non-specific symptoms that can appear from neonatal stages to adulthood. It is more frequently observed in Asians, with a prevalence of approximately 1 in 40,000 people. Accurate diagnosis requires a comprehensive clinical interview and laboratory examinations. This report presents the case of a 37-year-old woman with GS who also experienced a urinary tract infection and had a history of cesarean section. Upon admission, she reported feeling fatigued and weak in all extremities. She had undergone a cesarean section a month prior due to pre-eclampsia. Initial laboratory tests revealed hypokalaemia, hyponatremia, and hypochloraemia. Further evaluation during hospitalization detected a urinary tract infection, hypocalciuria, and hypomagnesemia. The patient also suffered from carpopedal spasms and muscle cramps. Treatment included magnesium sulfate, calcium gluconate, potassium chloride, and sodium chloride infusions to restore electrolyte balance. The patient was discharged after six days, with a diagnosis of Gitelman Syndrome, which was unusual given her late onset of symptoms, as most cases are identified in childhood. The clinical presentation was largely driven by the patient’s electrolyte imbalances, especially hypokalaemia and hypomagnesemia, with hypomagnesemia further contributing to hypocalcemia and vitamin D deficiency. The patient’s symptoms improved after appropriate electrolyte supplementation. This case emphasizes the importance of a detailed clinical history and laboratory assessments in diagnosing GS, along with timely correction of electrolyte disturbances to improve the patient’s condition and prevent complications.